2001
DOI: 10.1128/aac.45.2.525-531.2001
|View full text |Cite
|
Sign up to set email alerts
|

Clinafloxacin versus Piperacillin-Tazobactam in Treatment of Patients with Severe Skin and Soft Tissue Infections

Abstract: Patients (n ‫؍‬ 409) with severe skin and soft tissue infections (SSTIs) were randomized to receive clinafloxacin or piperacillin-tazobactam (plus optional vancomycin for methicillin-resistant cocci), administered intravenously, with the option to switch to oral medication. Most patients had cellulitis, wound infections, or diabetic foot infections. Staphylococcus aureus, Enterococcus faecalis, and Pseudomonas aeruginosa were the most common baseline pathogens. Fewer baseline pathogens were resistant to clinaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 36 publications
(40 reference statements)
6
49
0
3
Order By: Relevance
“…In this study of CSSSIs, the cure rates among patients who received ertapenem and among patients who received piperacillin-tazobactam were equivalent overall (82.4% vs. 84.4%) and similar to or somewhat higher than those reported in other, similarly designed clinical trials [15][16][17][18][19]. As shown by others, cure rates for foot infections associated with diabetes, which are often complicated by compromised vascularity, were lower for both treatment groups in this study.…”
Section: Discussionsupporting
confidence: 80%
“…In this study of CSSSIs, the cure rates among patients who received ertapenem and among patients who received piperacillin-tazobactam were equivalent overall (82.4% vs. 84.4%) and similar to or somewhat higher than those reported in other, similarly designed clinical trials [15][16][17][18][19]. As shown by others, cure rates for foot infections associated with diabetes, which are often complicated by compromised vascularity, were lower for both treatment groups in this study.…”
Section: Discussionsupporting
confidence: 80%
“…In the large pivotal skin/skin structure infection trial, ertapenem therapy had equivalent efficacy overall to piperacillin-tazobactam [3]. MSSA was the predominant pathogen in that trial, as has been reported in several similar trials [8][9][10][11][12]. The objective of this subgroup analysis of data from the pivotal skin/skin structure infection trial was to compare the efficacy of ertapenem with that of piperacillin-tazobactam in the treatment of serious staphylococcal infections and to examine the demographic and disease characteristics of patients with MSSA infection.…”
Section: Introductionmentioning
confidence: 75%
“…In two large studies comparing quinupristin/dalfopristin [11]. Additionally, in an open-label study of levofloxacin versus ticarcillin-clavulanate alone or followed by amoxicillin-clavulanate [12], clinical success rates for patients with S. aureus infection (presumably MSSA, since patients with infections caused by resistant bacteria were excluded) were 87.3% (48 of 55) for levofloxacin and 78% (39/50) for ticarcillin-clavulanate/amoxicillin-clavulanate 2-5 days post-therapy, an endpoint similar to the end of treatment assessment but considerably shorter than 10-21 days post-therapy test of cure assessment in the current report.…”
Section: Discussionmentioning
confidence: 99%
“…However, the length of piperacillin-tazobactam treatment described in published studies does not usually surpass 2 weeks [3][4][5], including some recent trials dealing with patients with diabetic foot infection [19,20]. Ruiz-Irastorza et al [18] explain these apparent differences in the marrow toxicity of piperacillin and piperacillin-tazobactam by the difference in the amount of the usual daily dose (12 g, in the case of piperacillin, and 16 g, in the case of piperacillin-tazobactam).…”
mentioning
confidence: 99%